The Effect Of Internal Control And Quality Of Accounting Information Systems On Quality Information On Pt. Pandu Siwi Sentosa (Pandu Logistics) - Oky Syahputra (Enrichment : Journal of Management, 2022)
This study aims to determine and analyze the effect of internal control and the quality of accounting information systems on the quality of information at PT. Pandu Siwi Sentosa (Pandu Logistics). This study uses a sampling technique in this study using a saturated sample. The research approach used in this research is quantitative research methods, the type of research used is descriptive quantitative research and the nature of the research used is descriptive explanatory research. The method of data collection is primary data obtained from users of accounting information systems at PT. Pandu Siwi Sentosa (Pandu Logistics). The population of this study were 66 users of accounting information systems. The samples used in this study were 66 samples of users of accounting information systems. Data processing with Smart PLS 3.0 Software. The results of the study partially, the internal control variable does not have a significant effect on the quality of information, while the variable Quality of Accounting Information Systems has a significant effect on the quality of information.